Implementasi dan Perancangan Sistem Pengelolaan dan Penyewaan Aset Berbasis Web dengan Algoritma Priority Scheduling Queue dan First In First Out (FIFO) untuk PT Indonesia Comnets Plus - Lukas Lukas; Anita Ratnasari (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
The IT asset rental at PT Indonesia Comnets Plus has been facing issues with data fragmentation and conflicts in logistics distribution priorities. This study aims to develop a web-based asset management information system using the Laravel 10 framework and MVC architecture. The main solution implemented is a hybrid scheduling mechanism that integrates the Multilevel Feedback Queue (MFQ) and First In First Out (FIFO) algorithms. MFQ groups delivery queues into three priority levels based on rental dates, while FIFO ensures fair distribution within the same priority level. Function testing using Black Box Testing across five key scenarios, including Midtrans integration, a daily return penalty of 3.5%, and a due date penalty of 2%, showed 100% validity. This system successfully improves logistics efficiency and clarifies contract transparency.